Low-dose photon irradiation induces invasiveness through the SDF-1α/CXCR4 pathway in malignant mesothelioma cells - Yamauchi, Yoshikane; Safi, Seyer; Orschiedt, Lena; Gardyan, Adriane; Brons, Stephan; Hörner-Rieber, Juliane; Nicolay, Nils; Huber, Peter E.; Eichhorn, Martin E.; Dienemann, Hendrik; Herth, Felix; Weber, Klaus-Josef; et al. (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.19134 Yoshikane Yamauchi, Seyer Safi, Lena Orschiedt, Adriane Gardyan, Stephan Brons, Juliane Rieber, Nils H. Nicolay, Peter E. Huber, Martin Eichhorn, Hendrik...
Gesehen am 03.04.2018